Uses and protein content of green guaje seeds (Leucaena leucocephala (Lam.) de Wit offered in the markets of Southern Puebla State, Mexico - Reyes-Matamoros, Jenaro; Martínez-Moreno, David; López-Morales, Dolores (Ecological Questions, 2025)
Leucaena leucocephala, commonly known as guaje, is a woody plant endemic to Mexico with edible seed pods. Despite its historical significance as a resource for Mesoamerican peoples, the nutritional value of guaje remains poorly documented. This study aims to explore the uses and protein content of green guaje seeds offered in markets in Southern Puebla State, Mexico. The research involved interviewing vendors at various markets in Southern Puebla, including Tepeaca tianguis, Revolución market, La Rotonda market, and El Moralillo tianguis, where a total of 127 stalls were surveyed. Information was gathered regarding the source, uses, and preparation of guaje seeds. Additionally, the protein content of the seeds was analyzed to determine its nutritional value. Green guaje seeds were available at diverse sales points, with distinct vendor profiles: regatoneros (local resellers) predominantly at the Revolución and La Rotonda markets, while self-producing vendors were more common at Tepeaca tianguis. Eleven culinary preparations featuring guaje were identified, with guaxmole being the most prevalent (40.66%) and various chili sauces with guaje following (38.52%). Although most vendors were unaware of the medicinal uses of guaje seeds, a few recognized their traditional applications, including as a dewormer and for alleviating coughs, stomach pains, and cramps. The protein content in guaje seeds varied significantly, ranging from 6.991 µg/µl in seeds from San Pablo Zoyatitlanapan at the Revolución market to 22.3766 µg/µl in seeds from Acatzingo at the Tepeaca tianguis. This study highlights the underutilized potential of guaje seeds and provides valuable information on their protein content and culinary uses. The significant variability in protein content based on the seed's origin underscores the need for further research into factors affecting nutritional quality. Additionally, increased awareness of guaje's medicinal properties could enhance its utilization and benefits in local communities.